Pengaruh Penggunaan Model Problem Based Learning (pbl) Terhadap Motivasi Belajar Dan Perilaku Prososial Siswa Pada Pembelajaran Pai Sdn 82 Kota Bengkulu - Pahlawan, Pahlawan; Adisel, Adisel; Chandra, Pasmah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
This study aims to examine the impact of the Problem - Based Learning ( PBL ) model on students ' learning motivation and prosocial behavior in Islamic Education at SDN 82 Bengkulu City . The research is a quantitative study , using a quasi - experimental design known as " the matching - only pretest - posttest control group design . " The population includes all students at SDN 82 Bengkulu City , with the sample selected through random sampling . The experiment was conducted in class VD ( experimental group ) and class VB ( control group ) . Research instruments included questionnaires assessing learning motivation and prosocial behavior , administered both at the beginning ( pretest ) and end ( posttest ) of the experiment for both groups . Data analysis was conducted using quantitative techniques , including both descriptive and inferential statistics , with the t - test used for hypothesis testing . The t - test results showed that the gain score for students learning motivation was 6.79 , while for prosocial behavior it was 15.77 , compared to a critical t - value of 2.07 at a 5 % significance level . Statistically , this indicates that t - values for both learning motivation ( 6.79 ) and prosocial behavior ( 15.77 ) were greater than the critical t - value ( 2.07 ) , suggesting a significant positive impact . Thus , it can be concluded that the use of the Problem - Based Learning model significantly influences both learning motivation and prosocial behavior in Islamic Education at SDN 82 Bengkulu City . Keywords : Problem - Based Learning , Learning Motivation , Prosocial Behavior , Islamic Education